(untitled) (Biological Sciences - PJSIR, 2022)
The genus Tolumnia Sti’llfrom the Indo-Pakistan subcontinent is revised. Five species are keyed and described with special reference to their metathoracic scent gland complex, male and female genitalia and their relationships within the tribe Carpocorini Slill is also briefly discussed.